Flexible pressure sensor based on cigarette filter and highly conductive MXene sheets. (October 2021) - Li, Ran; Tian, Xiaohan; Wei, Min; Dong, Aijun; Pan, Xi; He, Yunlu; Song, Xuyan; Li, Hongfei
Abstract: Flexible and cost-effective MXene-cigarette filter (MCF) based pressure sensors are fabricated by dip-coating cigarette filters with Ti3 C2 T x MXene nanosheets in the aqueous dispersion. The resultant MCF sensors exhibit fast response to compression, and show excellent cycling stability (2500 cycles at 10% compression strain) in the radial direction, which is attributed to the highly intrinsic conductivity of MXene sheets and the oriented structure of cigarette filter. Moreover, the MXene coated fibers in the MCF can be simply torn off with adhesive tape to prepare wearable film sensors for detecting both bending and compression. Due to the high sensitivity and flexibility, the sensor demonstrates excellent performance in monitoring human behavior. Highlights: Pressure sensors were fabricated by dip-coating cigarette filters with MXene. The bulk sensor can be peeled off with tape to prepare wearable film sensors. The sensors exhibit fast response and excellent cycling stability.